2023
DOI: 10.1017/s0007114523000612
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional profile of commercial complementary foods in Japan: comparison between low- and high-price products

Abstract: Despite the increasing market share of commercial complementary foods, their nutritional characteristics and those associated with the price of products are still unknown in Japan. We compared the nutritional characteristics of commercially available complementary foods of different price levels in Japan. Data were obtained from the websites of Japanese brands of infant and young children’s food. Nutrient profiles (unit/100 g), ingredients, and food additives were compared between low- and high-priced products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…An assessment of CPCF launched into the European market between 2017 and 2021 found that 18.3% were CPCF finger foods/snacks (Grammatikaki et al, 2021 ) and a separate assessment of CPCF products available in the market in 2016–2017 across 10 European countries found 12.9% to be CPCF finger foods/snacks (Hutchinson et al, 2021 ). In Asia, a 2022 assessment of CPCF products available in Japan found over one‐quarter (25.4%) were CPCF finger foods/snacks (Sugimoto et al, 2023 ). The growth of CPCF finger foods/snacks can be understood in the context of consumers' growing demand for convenience and reliance on packaged, ready‐to‐eat foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of CPCF launched into the European market between 2017 and 2021 found that 18.3% were CPCF finger foods/snacks (Grammatikaki et al, 2021 ) and a separate assessment of CPCF products available in the market in 2016–2017 across 10 European countries found 12.9% to be CPCF finger foods/snacks (Hutchinson et al, 2021 ). In Asia, a 2022 assessment of CPCF products available in Japan found over one‐quarter (25.4%) were CPCF finger foods/snacks (Sugimoto et al, 2023 ). The growth of CPCF finger foods/snacks can be understood in the context of consumers' growing demand for convenience and reliance on packaged, ready‐to‐eat foods.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate addition of sugars and high sugar content have been noted among these products in other contexts. An assessment of CPCF products across Europe found that among CPCF sweet snacks/confectionery items, the contribution of total sugar to total energy ranged from 23% in Spain to 44% in the United Kingdom, and exceeded 20% for CPCF rusks/biscuits in four out of six countries (Hutchinson et al, 2021 ), and a study of CPCF products available for online purchase in 2022 in Japan found that 84% of CPCF finger foods/snacks contained at least one added sugar (Sugimoto et al, 2023 ). The presence of added sugars and total sugar content of CPCF finger foods/snacks will vary by type of product within this category—a study of CPCF available in the United States found mean total sugar content of CPCF cereal bars/pastries, grain‐based desserts, dairy‐based desserts and savoury snacks to be 25, 12, 11 and 7 g per 100 g product, respectively, with 97%, 95%, 71% and 44% of these products containing an added sugar (Maalouf et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Commercial baby foods are discouraged because of concerns about their nutrient content, ingredient composition, flavour/taste, texture, and limited variety. Several studies in low-, middle-, and high-income countries have found that a large proportion of commercial baby foods have high sugar and sodium content and are low in iron [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. We have previously reported that the ingredients used in the formulation of commercial baby foods are predominantly sweet.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of foods low in nutrients and high in fat, sugar, and salt in infancy is associated with the double burden of malnutrition in low- and middle- income countries [ 19 , 20 ] and with higher energy intake and weight-for-length z scores in more affluent countries [ 21 ]. Other aspects of concern include the price of commercial baby foods; this is often higher compared to homemade foods [ 15 ]. Nonetheless, a large proportion of infants are offered commercial baby foods on a regular basis; for example, in Scotland, 41% of mothers of 8–12-month-old infants reported feeding them commercial baby foods on five or more days per week, and 24% stated that they gave their children “treats” as a snack at least once a day (these included chocolate buttons, ice cream, crisps, and cheese puffs) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPCF purées/meals are smoother in texture and their labels often display or state a range of foods such as vegetables, fruits, and meats—enabling the perception that they are both healthy and allow an introduction of a range of flavours to older IYC. However, some CPCF purées/meals present undesirable nutrient profiles, with many having high total sugar and/or sodium content (Bridge et al, 2021 ; Crawley & Westland, 2017 ; Hutchinson et al, 2021 ; Koletzko et al, 2018 ; Maalouf et al, 2017 ; Sugimoto et al, 2023 ; Walker & Goran, 2015 ). In addition, products are frequently promoted as appropriate from 4 months of age, despite the World Health Organization's (WHO) recommendation to exclusively breastfeed for the first 6 months of life (Bridge et al, 2021 ; Crawley & Westland, 2017 ; Sweet et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%